2019
DOI: 10.1002/brb3.1380
|View full text |Cite
|
Sign up to set email alerts
|

Children's physiological reactivity in emotion contexts and prosocial behavior

Abstract: Introduction Building on prior evidence that prosocial behavior is related to the regulation of personal distress in difficult situations, and given that physiological regulation is a central contributor to effective emotion regulation, this investigation evaluated whether and how children's autonomic nervous system (ANS) reactivity during emotion challenges influenced later expressions of prosocial behavior. Methods The current study utilized a diverse sample of school‐aged children (N = 169; 47.9% female; 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 89 publications
0
14
0
1
Order By: Relevance
“…First, studies have not focused on compassionate caregiving practices that are posited to be important for healthy parent-child relationships implicated in children’s own prosocial development ( Grusec et al, 2000 ; Mikulincer and Shaver, 2005 ; Hastings et al, 2015 ). Second, prior studies have primarily focused on children’s PNS activity at rest or in response to challenging or stressful contexts rather than tasks that provide children with opportunities to experience prosocial emotions and to engage in prosocial behaviors (e.g., Eisenberg et al, 1991 ; Miller et al, 2015 , 2016 ; Coulombe et al, 2019 ). Third, the existing research on biopsychosocial models of prosocial development has relied almost completely on questionnaire measures of prosocial behaviors and development.…”
Section: Introductionmentioning
confidence: 99%
“…First, studies have not focused on compassionate caregiving practices that are posited to be important for healthy parent-child relationships implicated in children’s own prosocial development ( Grusec et al, 2000 ; Mikulincer and Shaver, 2005 ; Hastings et al, 2015 ). Second, prior studies have primarily focused on children’s PNS activity at rest or in response to challenging or stressful contexts rather than tasks that provide children with opportunities to experience prosocial emotions and to engage in prosocial behaviors (e.g., Eisenberg et al, 1991 ; Miller et al, 2015 , 2016 ; Coulombe et al, 2019 ). Third, the existing research on biopsychosocial models of prosocial development has relied almost completely on questionnaire measures of prosocial behaviors and development.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic regulation was measured by several derived cardiac regulatory markers, including basal (resting) indicators, task‐related indicators, changes between basal and task, and changes during tasks. Most studies to date have focused on basal and/or task‐related reactivity (Calkins, 1997; Coulombe et al., 2019; Hinnant & El‐Sheikh, 2009; Holzman & Bridgett, 2017; Kahle et al., 2018; Sturge‐Apple et al., 2016; Sulik et al., 2015). The current study found no associations between pretask values and physiologic response to task (pretask to task change) and delay ability.…”
Section: Discussionmentioning
confidence: 99%
“…Children who delayed showed a smaller increase in HR and a greater decrease in RSA from the start of the task to the end of the task than children who did not delay. Efficient suppression of vagal tone is necessary when attention is required for coping with environmental demands, often resulting in a decrease in RSA (and thereby an increase in HR) in response to a challenge (Coulombe et al., 2019; Hinnant & El‐Sheikh, 2009; Porges et al., 2007). The association between HR and RSA changes during the task and children's successful delay of gratification is likely an indicator of effective vagal tone suppression in response to adapting to challenging stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because parents are the first model that children see and imitate. Modeling has a strong relationship of how patterns of thinking and behavior are formed based on the identification of models in the family, especially the figures of parents who tend to be role models of children (Coulombe, Rudd & Yates, 2019).…”
Section: Introductionmentioning
confidence: 99%